KETOKOHAN IBN MISKAWAIH DALAM BIDANG PENDIDIKAN KARAKTER - Mudzakkir Ali; Muh Syaifuddin (Universitas Wahid Hasyim Semarang, 2020)
Abstract In the mid of widespread radicalism in society, it has become a concern of many circles, especially eduacation expert. Various concept of deradicalization were presented in various media in order to create a conducive situation in society. Ibn Miskawaih can be seen as the first character to propose the concept of the middle path (moderate) as a character value that reject the minus and plus extrimities. It is necessary to reveal his concept in the field of character education. Keywords: Ibn Miskawaih and Character Education Abstrak Di tengah maraknya paham radikal di masyarakat, menjadi keprihatinan banyak kalangan, terutama para ahli pendidikan. Berbagai konsep deradikalisasi disuguhkan di berbagai media guna mewujudkan situasi kondusif di masyarakat. Ibn Miskawaih dapat dipandang sebagai tokoh pertama yang menyodorkan konsep jalan tengah (moderat) sebagai nilai karakter yang menolak ekstrimitas minus dan ekstrimitas plus. Di sinilah perlunya mengungkap kembali konsep Dia di bidang pendidikan karakter. Kata Kunci: Ibn Miskawaih dan Pendidikan Karakter